Reconsideration on the concept model of throat aurora - Desheng Han; Huixuan Qiu; Run Shi (地球与行星物理论评, 2022)
The solar wind-magnetosphere-ionosphere coupling driven by the solar wind is a systematic process that involves the buffering of magnetosheath and the response and feedback of magnetosphere and ionosphere. The driving effect of the solar wind has been analyzed in many previous observational studies, but the research on the contribution of magnetosheath and the feedback of magnetosphere and ionosphere is insufficient. Near magnetic local noon, discrete and diffuse auroras correspond to the processes occurring outside and inside the magnetosphere, respectively. Throat aurora is a particular discrete auroral form that only occurs near local noon, and its orientation is generally consistent with the direction of ionospheric convection, which is closely associated with the stripy diffuse aurora that is also along with the convection. This implies that the generation of throat aurora may be affected by factors inside the magnetosphere. At the same time, the occurrence rate of throat aurora is related to radial interplanetary magnetic field (IMF) conditions, indicating that its generation is also affected by factors outside the magnetosphere. In addition, a series of observations have shown that throat auroras correspond to the magnetopause indentations, accompanied by clear magnetopause reconnection signatures. In order to systematically explain all these observational results, a conceptual model of throat aurora proposed earlier is modified in this paper. The modified model suggests that the effect of ionospheric feedback on magnetopause reconnection is the key to the generation of magnetopause indentations, and the high-speed jets generated in the magnetosheath under radial IMF may only play a role in triggering the reconnection. This model synthetically considers the influence of factors inside and outside the magnetosphere on the solar wind-magnetosphere-ionosphere coupling, which may provide a new perspective for the comprehensive understanding of this process.